Industrial organisation, employment and labour regulations: Understanding recent changes in India - Damodaran, Sumangala (The India Journal of Labour Economics)
The article takes stock, along with the key arguments that have animated labour regulation and deregulation debates (leading to the recent developments), of the changes that have come to characterise the world of work in terms of industrial organisation (the extent and kinds of outsourcing arrangements between enterprises and companies, the profiferation of the service economy), employment arrangements (short term, irregular, contract, and various other kinds), and spatiality (work from home, gig work, digital work) in India. It addresses the following questions: Does the world of labour deregulation interact with the ways in which work and employment are structured and changes that have occurred in an industrial organisational sense in India? Can labour regulations, as they have unfolded in recent times, protect labour in the context of a multiplicity of organisational changes that have occurred in recent years?- Reproduced